Pemanfaatan Media Penyuluhan Gizi Lembar Balik oleh Dokter Kecil Dalam Program UKS Di Sekolah Dasar Kecamatan Sukawati Kabupaten Gianyar Tahun 2019 - I Putu Suiraoka; GA Dewi Kusumayanti (Poltekkes Kemenkes Denpasar, 2020)
This program focuses on health education activities by little doctors using applicative extension media in terms of applying food diversity, selecting healthy snacks and eating breakfast. The purpose of this community service activity is to conduct training and measure changes in the knowledge of small doctors before and after the training on the use of flipchart nutrition counseling media by little doctors in the UKS program. The targets in this activity are Little Doctors in SD N 1, SDN 2 and SDN 3 Batubulan Kangin. Community service activities were carried out in July 2019 which included pre-test, training, post-test, counseling with a flip sheet by a small doctor to target elementary school children in their neighborhood. The number of targets in the three elementary schools is 57 people. Descriptively the age of the small doctor ranged from 9 years to 12 years, with an average age of 10.33 years and a standard deviation of 0.76 years. The knowledge pre-test results show the lowest value of 45 and the highest value of 95 with an average of 72.45 and a standard deviation of 12.50. In counseling training activities using flipchart media on little doctors in SD N 1, 2 and 3 Batubulan miss it can be observed that the small doctors are very enthusiastic to follow and try. This is because the flipchart is something new and is easily applied by them. The results of the post-test knowledge showed an increase compared to the pre-test data. The lowest value is 50 and the highest value is 100 with an average of 76.05 and a standard deviation of 11.79. There was a significant increase in knowledge based on paired t test results (p 0.05). Based on a review of the results of community service activities, it can be suggested that counseling activities carried out by small doctors are more often done. This adds to the knowledge and insight of elementary school children about healthy, nutritious and balanced food. Counseling is done more easily by using flipchat Keywords: Nutrition education, Litle doctors, Flipchart, School Health Program